Profiling the Cymbopogon nardus Ethanol Extract and Its Antifungal Potential against Candida Species with Different Patterns of Resistance - de Toledo, Luciani G. [UNESP]; Ramos, Matheus A.S. [UNESP]; Spósito, Larissa [UNESP]; Castilho, Elza M. [UNESP]; Pavan, Fernando R. [UNESP]; Lopes, Érica O. [UNESP]; da Silva, Isabel C. [UNESP]; Zocolo, Guilherme J. [UNESP]; Ribeiro, Paulo R.V.; Oda, Fernando B. [UNESP]; Pereira, Juhan A.S. [UNESP]; dos Santos, André G. [UNESP]; et al. (Sociedade Brasileira de Quimica (SBQ), 2020)
The essential oil of Cymbopogon nardus, citronella, has been extensively studied. However, the chemical and biological properties of the ethanolic extract (EE) of C. nardus have not been evaluated. The aim of this study was to characterize the chemical composition of the EE of C. nardus and its active fraction (FrD). Moreover, the cytotoxic and antifungal properties of these extracts against Candida species with different resistance profiles to conventional drugs were evaluated. The compounds identified in EE were mono-C- and di-C-glycosyl flavones and phenylpropanoid glycosides. Phenylpropanoid glycosides were identified in FrD. EE showed antifungal activity, with minimum inhibitory concentration (MIC) values ranging from 62.5 to 500 µg mL-1. FrD was more effective against C. glabrata, as evidenced by the lowest MIC value (15.6 µg mL-1). EE inhibited yeast growth similar to amphotericin-B, as demonstrated by similar time-kill curves. EE inhibited C. albicans hyphae formation and mature biofilm of C. albicans, C. krusei and C. parapsilosis. The results of the chemical and biological analyses of EE and its fractions provided novel information and may contribute to control of infections caused by Candida species.
Keywords: Antifungal activity; Candida spp; Cymbopogon nardus; Ethanol extract; Flavones; Phenylpropanoids